Konkurrenceidræt i defensiven - Larsen, Knud (Forum for Idræt, 2001)
Competitive sport on the defensive Competitive sport has been characterised by almost constant expansion ever since it originated over a century ago. An everincreasing number of competitors and an ever-increasing public have made it one of our greatest mass movements, not only in Denmark but in most other parts of the world. The development that can be seen in a number of the key figures of competitive sport during recent years suggest, however, that the upward growth curve may have broken and that the interest of Danish people for competitive sport as a historically new phenomenon has begun to recede. A comparative analysis of figures from the Culture and Leisure Studies at the Institute for Social Research in 1987, 1993 and 1998 show that fewer and fewer Danes over the age of 15 are interested in the world of competitive sport either as active participants or as its public in the form of spectators at sporting events and of sports programmes on television.